Analisis PCK Guru IPA Kelas VII SMP Negeri se-Kecamatan Banyudono Kabupaten Boyolali dalam Penyusunan Perangkat Pembelajaran - Putri Agustina; Amalia Luthfi Yudiantari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
Teachers are one of the important components that determine the success of learning. There are several competencies that must be mastered by a teacher, including professional competency (subject matter content) and pedagogical competency. The integration of knowledge about learning material content with knowledge about pedagogy is known as PCK (Pedagogical Content Knowledge). The aim of this research is to determine the ability of Pedagogical Content Knowledge (PCK) of class VII science teachers at State Middle Schools in Banyudono District, Boyolali Regency in preparing lesson plans. This research is descriptive research carried out at State Middle Schools in Banyudono District, Boyolali Regency. The population of this study were all class VII science teachers at State Middle Schools in Banyudono District, while the sample was 3 class VII science teachers at State Middle Schools in Banyudono District, Boyolali Regency, taken using population sampling. Data collection techniques using documentation techniques. PCK identification is carried out using an identification sheet. The aspects identified include CK (Content Knowledge), PK (Pedagogical Knowledge), and PCK (Pedagogical Content Knowledge). Based on the research that has been carried out, the results show that CK mastery ability is in the quite good category with an average of 74%, PK is in the quite good category with an average of 57%, and PCK is in the good category with an average of 88%.